The geodiversity site of Geopark Ranah Minang Silokek, Indonesia: Promoting geo-education and geotourism through geosite assessment - Ratna Savira Adrianda; Rina Sahara; Ugi Kurnia Gusti (International Journal of Geoheritage and Parks)
Geopark Ranah Minang Silokek holds unique and diverse geodiversity, encompassing geomorphology, sedimentology, stratigraphy, paleontology, tectonic, structural geology, and complex geological history. This area promises potential to be recognized as a UNESCO Global Geopark, with a geological rock spanning Pre-Tertiary and Neogene epochs. The study focused on assessing 14 prominent geosites to quantitatively evaluate their geological significance, potential educational value, touristic value, degradation risks, and intrinsic values. The study's main goal was to globally promote the area's rich geoheritage among the public and geoscientists. Results from this assessment categorized Geopark Ranah Minang Silokek within the moderate-high value range, with the Silokek Karst Complex and Granit of Sangkiamo identified as high-value geosites. Our study identified that there were 5 geological phases that could be studied and observed in the Geopark Ranah Minang Silokek. The findings underscored the geopark's potential for educational and tourism purposes, highlighting its suitability as a pioneering geo-education site and earth science field laboratory in Sumatra, Indonesia. This study also highlighted future initiatives which would include designing geotourism activities and educational programs within Geopark Ranah Minang Silokek and beyond.